2019
DOI: 10.1002/lno.11135
|View full text |Cite
|
Sign up to set email alerts
|

Algal scavenging of mercury in preindustrial Arctic lakes

Abstract: The geochemical speciation of total mercury (THg) was examined in pre-1800 Arctic lake sediments to improve understanding of the factors controlling "natural baseline" THg. Solid-phase binding forms of THg were determined by sequential extraction of dated cores from three lakes in different ecozones (barren tundra, grassy tundra, and boreal forest). Sediment organic matter (OM) was mostly of algal origin. Mercury was highly concentrated in the sediment OM fraction (OM-Hg), comprising 60-87% of THg, while OM (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 77 publications
5
16
0
Order By: Relevance
“…Our results showed that differences in atmospheric Hg deposition fluxes, catchment area, or erosional fluxes cannot explain the high Hg accumulation rates in the HZ lakes. Similar to what has been observed in other lakes (Biester et al 2018; Outridge et al 2019) or the ocean (Zaferani et al 2018), we suggest that water column Hg scavenging by sinking algal OM strongly increases Hg export from the water phase to the sediment in the HZ lakes. The chemical composition of the trap material of the HZ lakes (low C/N ratios, polypeptides, amides, and proteins indicated by the FTIR spectra) as well as in the water phase (high pH, low nitrate) gives a clear indication that OM in the HZ lake sediments is dominated by algal‐derived OM in contrast to the BF lakes, where most OM is derived from catchment soils (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results showed that differences in atmospheric Hg deposition fluxes, catchment area, or erosional fluxes cannot explain the high Hg accumulation rates in the HZ lakes. Similar to what has been observed in other lakes (Biester et al 2018; Outridge et al 2019) or the ocean (Zaferani et al 2018), we suggest that water column Hg scavenging by sinking algal OM strongly increases Hg export from the water phase to the sediment in the HZ lakes. The chemical composition of the trap material of the HZ lakes (low C/N ratios, polypeptides, amides, and proteins indicated by the FTIR spectra) as well as in the water phase (high pH, low nitrate) gives a clear indication that OM in the HZ lake sediments is dominated by algal‐derived OM in contrast to the BF lakes, where most OM is derived from catchment soils (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that algae OM appear to dilute Hg concentrations in trap materials but also greatly enhance Hg accumulation rates. High Hg accumulation in sediments as a result of Hg scavenging by algal OM in the water column has been described in previous studies (Outridge et al 2007(Outridge et al , 2019Zhang et al 2014;Biester et al 2018;Zaferani et al 2018), although the source and mass balance of Hg in these studies was mostly unknown.…”
Section: Effect Of Soil Erosion On Sediment Hg Concentrations and Accumulation Ratesmentioning
confidence: 86%
See 2 more Smart Citations
“…In aquatic environments, warmer water temperature can increase primary production (Häder et al, 2014;Rantala et al, 2016), with potential indirect consequences on underwater solar radiations, dissolved oxygen and redox gradients (Paerl and Huisman, 2009;Sahoo and Schladow, 2008). These impacts can affect metal biogeochemistry by increasing the rate of biological sequestration of dissolved and particulate metals in lakes (Outridge et al, 2007;Outridge et al, 2019;Stern et al, 2009) and favor the mobility of metals in lake sediment (Boyle, 2001). The capacity of sediments to acquire more atmospheric Hg0 from the uptake by algae during periods of increased primary production is termed "algal scavenging" (Outridge et al, 2007).…”
Section: Impact Of Climate Change On Subarctic Metal Biogeochemical Cyclingmentioning
confidence: 99%